Optimalisasi Layanan Desa Pedawang Melalui Sistem Kearsipan - Mulyapradana, Aria; Aghus Jamaludin Kharis; Farikhul Muafiq; Safna Saqinah; Nafiatul Manahilkhakim (Penerbit Goodwood, 2025)
Purpose: This study aims to determine how an archive storage system can improve the quality of services offered by the Pedawang Village Office. Methodology: The subject of this study is the apparatus of Pedawang Village, which consists of four people. The indicators studied were reliability, tangibles, responsiveness, assurance, and empathy. Results: The study found that although the government of Pedawang village has used an archive management system, archive storage is still performed manually. Because of the lack of infrastructure and storage facilities, the number of documents is growing. Conclusion: Pedawang Village's archiving system is good, but needs to be improved through the archive life cycle. The main obstacles are limited facilities, accumulation of archives, and poor knowledge of the village officials. Solutions include improved facilities, digitization of archives, and archival training. Limitations: The study only covered one village (Pedawang); therefore, the results cannot be applied to other villages with different characteristics. Contribution: With limited physical storage facilities, using information technology to store archives can benefit the organization and maintain the quality of service, increasing public trust in the Pedawang Village Government.